2013
DOI: 10.1002/jor.22434
|View full text |Cite
|
Sign up to set email alerts
|

Geometric profile of the tibial plateau cartilage surface is associated with the risk of non‐contact anterior cruciate ligament injury

Abstract: The purpose of this study was to determine if geometry of the articular surfaces of the tibial plateau is associated with non-contact anterior cruciate ligament (ACL) injury. This was a longitudinal cohort study with a nested case-control analysis. Seventyeight subjects who suffered a non-contact ACL tear and a corresponding number of controls matched by age, sex, and sport underwent 3 T MRI of both knees. Surface geometry of the tibial articular cartilage was characterized with polynomial equations and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 28 publications
2
72
1
Order By: Relevance
“…Prior work has shown that increased posterior–inferior directed slope of the tibial plateau is associated with increased risk of suffering an ACL and ACL graft injury, and the increased lateral compartment posterior–inferior directed slopes found in the current study (3.6° for the ACL‐LM group and 1.6 for the ACL group) further exacerbates the chance of a second injury to the ACL graft . In addition, there is evidence that geometry of the articular cartilage and tibial plateau subchondral bone are associated with worsening cartilage degenerative changes in the lateral tibial plateau .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Prior work has shown that increased posterior–inferior directed slope of the tibial plateau is associated with increased risk of suffering an ACL and ACL graft injury, and the increased lateral compartment posterior–inferior directed slopes found in the current study (3.6° for the ACL‐LM group and 1.6 for the ACL group) further exacerbates the chance of a second injury to the ACL graft . In addition, there is evidence that geometry of the articular cartilage and tibial plateau subchondral bone are associated with worsening cartilage degenerative changes in the lateral tibial plateau .…”
Section: Discussionsupporting
confidence: 51%
“…Characterization of the position of the tibia relative to the femur during MRI acquisition was accomplished by establishing three‐dimensional, bone‐based coordinate systems within the femur and tibia (Fig. ) . The following three‐dimensional (3D) measurements of the geometry of the tibial articular cartilage surface, underlying tibial subchondral bone, and meniscus were made relative to the 3D bone‐based coordinate systems using the approaches that have been described (Table ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second phase focused on a multivariate evaluation of knee-joint geometry and its effect on the risk of ACL injury. [16][17][18][19][20][21] Detailed results from the first phase are currently under review for publication and, consequently, we can provide only an overview of the study design, but we encourage the reader to consider the detailed findings once they have been published. The findings from the multivariate work in the second phase have been published.…”
Section: Development Of Acl Injury Risk Modelsmentioning
confidence: 99%
“…The findings from the multivariate work in the second phase have been published. [16][17][18][19][20][21] Athletes from 36 institutions (8 colleges, 28 high schools) were monitored prospectively over 4 years for the occurrence of ACL injuries. A total of 109 case participants (70 females, 39 males) who sustained a first-time grade III noncontact ACL injury during involvement in a schoolorganized sport were enrolled in the study.…”
Section: Development Of Acl Injury Risk Modelsmentioning
confidence: 99%